2021
DOI: 10.1007/s00204-021-03008-0
|View full text |Cite
|
Sign up to set email alerts
|

Integration of transcriptome analysis with pathophysiological endpoints to evaluate cigarette smoke toxicity in an in vitro human airway tissue model

Abstract: Exposure to cigarette smoke (CS) is a known risk factor in the pathogenesis of smoking-caused diseases, such as chronic obstructive pulmonary diseases (COPD) and lung cancer. To assess the effects of CS on the function and phenotype of airway epithelial cells, we developed a novel repeated treatment protocol and comprehensively evaluated the progression of key molecular, functional, and structural abnormalities induced by CS in a human in vitro air–liquid-interface (ALI) airway tissue model. Cultures were expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…The oxidative status of the cell can also be evaluated by measuring reduced glutathione (GSH) levels, which are decreased under oxidative stress conditions. GSH is measured in cell lysates using spectrophotometry [25,26,28,31,33,41,53,84,85,89,97], liquid chromatography coupled to mass spectrometry (LC-MS) [97], enzymatic methods [51] and fluorescence [87]. Custom-made or commercially available kits can be used [42,44].…”
Section: Methods For Detecting Oxidative Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…The oxidative status of the cell can also be evaluated by measuring reduced glutathione (GSH) levels, which are decreased under oxidative stress conditions. GSH is measured in cell lysates using spectrophotometry [25,26,28,31,33,41,53,84,85,89,97], liquid chromatography coupled to mass spectrometry (LC-MS) [97], enzymatic methods [51] and fluorescence [87]. Custom-made or commercially available kits can be used [42,44].…”
Section: Methods For Detecting Oxidative Stressmentioning
confidence: 99%
“…Oxidative stress is also responsible for protein carbonylation. The intracellular level of protein carbonyls can be detected either by ELISA [97] or immunoblotting assays [10]. Other products of oxidative stress (3-nitrotyrosine (3-NT), 8-isoprostane and 8-hydroxydeoxyguanosine) can be detected using enzymatic immunoassays [44,88,90].…”
Section: Methods For Detecting Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study reported that ACE2 was significantly overexpressed in the bronchial and alveolar epithelial cells in smokers, independent of age or gender, indicating that CS related ACE2 overexpression may assist the SARS-CoV-2 infection, and smoking cessation may potentially attenuate the risk of COVID-19 transmission (173). An in vitro air-liquid-interface (ALI) human airway tissue model was successfully developed to assess the effects of CS on the function and phenotype of airway epithelial cells in smokers, including xenobiotic metabolism, oxidative stress, and inflammatory responses (174).…”
Section: Cs Associated Inflammation and Immunosuppression In Lung Cancermentioning
confidence: 99%